2017
DOI: 10.1016/j.celrep.2017.06.083
|View full text |Cite|
|
Sign up to set email alerts
|

Deletion of GLUT1 and GLUT3 Reveals Multiple Roles for Glucose Metabolism in Platelet and Megakaryocyte Function

Abstract: Summary Anucleate platelets circulate in the blood to facilitate thrombosis and diverse immune functions. Platelet activation leading to clot formation correlates with increased glycogenolysis, glucose uptake, glucose oxidation, and lactic acid production. Simultaneous deletion of glucose transporter (GLUT) 1 and GLUT3 (double knockout (DKO)) specifically in platelets completely abolished glucose uptake. In DKO platelets mitochondrial oxidative metabolism of non-glycolytic substrates such as glutamate, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…AIF1v1, on the other hand, seems to be involved in glucose metabolism and platelet activation suggesting a role in platelet glycolysis, but there is no data in the literature regarding this particular isoform. Glucose metabolism plays a critical role in the production, activation, and survival of platelets according to a recent study [ 40 ] and relationships between tumor and the hemostatic system is being recognized as an important BC regulator [ 41 ]. Considering these results, the potential roles and characterization of AIF1 were further explored.…”
Section: Resultsmentioning
confidence: 99%
“…AIF1v1, on the other hand, seems to be involved in glucose metabolism and platelet activation suggesting a role in platelet glycolysis, but there is no data in the literature regarding this particular isoform. Glucose metabolism plays a critical role in the production, activation, and survival of platelets according to a recent study [ 40 ] and relationships between tumor and the hemostatic system is being recognized as an important BC regulator [ 41 ]. Considering these results, the potential roles and characterization of AIF1 were further explored.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Fidler and coworkers demonstrated that SOD2-KO platelets showed increased mitochondrial ROS; however, total platelet ROS content remained unchanged. Furthermore, deletion of SOD2 did not alter tail-bleeding or arterial thrombosis in vivo, suggesting that SOD2 is dispensable for platelet redox balance [ 81 , 82 ].…”
Section: Endogenous and Exogenous Antioxidant Systems As Regulatormentioning
confidence: 99%
“… 21 28 GLUT3 is also expressed in lymphocytes, monocytes, macrophages, and platelets where it is stored in the intracellular vesicles and, when needed for an increase in glucose demand, it can be translocated and fused to the plasma membrane upon cellular activation. 6 , 29 In the structural studies of GLUTs that are resolved to atomistic resolutions only recently, multiple crystal structures of GLUT3 have been determined, 30 all in the outward-open/occluded (exofacial) conformations but none inward-open/occluded (endofacial). Interestingly, multiple crystal structures of GLUT1 are currently available in the endofacial conformations 31 , 32 but none exofacial.…”
Section: Introductionmentioning
confidence: 99%